Transação tributária e os limites da Fazenda Pública - Comper, Guilherme Rafael (2024)
The purpose of this study is to analyze federal tax transactions and the limits imposed by the Public Treasury on their execution. First, the study provides a brief overview of extrajudicial means of conflict resolution, their emergence in law, importance, modalities, and characteristics. Next, the legislative evolution of tax transactions is analyzed until Law No. 13,988/2020 is reached. After that, the guiding principles are analyzed, proceeding to examine their legal nature as a contract or an administrative act. Next, the unavailability of the public interest and tax transactions are explored, according to administrative acts. Regarding Law No. 13.988/2020, the four modalities provided for in the legislation are analyzed. Finally, the limitations on the execution of tax transactions in the National Tax Code, in Law No. 13.988/2020, and the challenges and future perspectives are analyzed